Collection and conservation of extinct land races of rice from Raigarh district of Chhattisgarh - Mangla, Parikh; Sharma, Bhawana; Chaudhari, Prabha R; Bhandarkar, Sandeep; Sharma, Deepak (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> An exploration trip was conducted during kharif 2012-13 for the collection of rare and valuable rice land races from different blocks of raigarh district. A total of 97 landraces were collected by the exploration team from 41 villages of four different blocks viz., Tamnar, Gharghoda, Lailunga and Dharamjaigarh from Raigarh district. Based on the morphological and quality characters the diverse landraces were collected. The valuable landrace conserved by farmers namely, Borojhari, Boonde, Geeta, Saria, Thadvel, Bathras, Agiasal, Ratanchuri, Goirmal, Pangudi, 90 No., Ganga and Sonakathi. These valuable landraces possesses the characterstics such as fine grain, aroma, red pericarp, early maturity, submergence tolerance and good head rice recovery. The collected landraces will be utilized for the genetic enhancement and value addition of existing varieties of rice. Thus, it may be helpful not only in conserving the genetic resources but also exploit their potential in terms of yield and other quality characters. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->